Energetic hybrid polymer network (EHPN) through facile sequential polyurethane curation based on the reactivity differences between glycidyl azide polymer and hydroxyl terminated polybutadiene. Issue 13 (26th January 2016) - Tanver, Abbas; Rehman, Fida; Wazir, Aisha; Khalid, Syed; Ma, Song; Li, Xiaoyu; Luo, Yunjun; Huang, Mu-Hua
Abstract : To improve the thermo-mechanical properties of glycidyl azide polymer and hydroxyl terminated polybutadiene based propellants, a facile sequential polymerization approach was used to prepare an energetic hybrid polymer network by stepwise curation. Abstract : To improve the thermo-mechanical properties of glycidyl azide polymer (GAP) and hydroxyl terminated polybutadiene (HTPB) based propellants, a facile sequential polymerization approach has been conducted to prepare an energetic hybrid polymer network (EHPN) through stepwise curation. The detailed curing conditions for the EHPN formation were determined using an in situ FTIR kinetic study. The effect of curing ratio (NCO/OH) on the mechanical properties of the polyurethane networks of GAP and HTPB was investigated, wherein hexamethylene diisocyanate biuret trimer (Desmodur N100) and isophorone diisocyanate (IPDI) were used as mixed curative agents. A series of EHPNs were prepared by varying the relative weight ratios of GAP and HTPB with a single poly-isocyanate mixed curing system (IPDI/N100). A remarkable mechanical strength of up to 5.83 MPa and an elongation at break of 359% were achieved with a 50 : 50 weight ratio of GAP to HTPB, which is the maximum mechanical strength reported thus far for a binder system of GAP and HTPB, which has a thermally more stable cross-linked network. The thermal properties of the as-synthesized PU networks of GAP, HTPB and GAP–HTPB EHPNs with different weight ratios were characterized using the DMA and DSC techniques. Thermal degradation behavior and morphological studies were also investigated with TGA-DTG and scanning electron microscopy (SEM), respectively. The facile sequential polyurethane curation polymerization technique can be potentially used for advanced solid composite propellants.